IMPLEMENTATION OF BUERGER ALLEN EXERCISE TO IMPROVE PERIPHERAL PERFUSION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS: A CASE STUDY - Khirniq Qiqi Milataki; Ida Mardalena; Abdul Majid; Catur Budi Susilo (CV. Fahr Publishing, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease that may lead to impaired peripheral perfusion due to reduced blood flow to the extremities, thereby increasing the risk of diabetic foot ulcers and amputation. Buerger Allen Exercise (BAE) is a non-pharmacological nursing intervention that can be implemented to improve peripheral circulation. This case study aimed to describe the implementation of Buerger Allen Exercise in patients with Diabetes Mellitus experiencing ineffective peripheral perfusion. A descriptive case study design was employed using the nursing process approach involving two patients with Diabetes Mellitus. Buerger Allen Exercise was administered twice daily for three consecutive days. The intervention outcomes were evaluated using the Ankle Brachial Index (ABI), Capillary Refill Time (CRT), peripheral pulse strength, skin temperature, and skin color. The findings demonstrated an improvement in ABI values in the first patient from 0.883 to 0.910 in the right leg and from 0.891 to 0.918 in the left leg. In the second patient, ABI increased from 0.867 to 0.892 in the right leg and from 0.879 to 0.901 in the left leg. Both patients also showed improvement in CRT from >3 seconds to ≤2 seconds, accompanied by stronger peripheral pulses, warmer extremities, and more normal skin color. In conclusion, the implementation of Buerger Allen Exercise as part of nursing care improved indicators of peripheral perfusion in both patients and has the potential to serve as a non-pharmacological nursing intervention to support peripheral perfusion in patients with Diabetes Mellitus.